(untitled) (Research, Society and Development, 2022)
This study aimed to understand the indexes, the age group of the victims, and the reasons that lead to accidents, such as infractions, speeding, alcoholic beverages and the damage that traffic accidents cause, not only for the victims and their families, as well as damage to public health, so that Brazil occupies the fifth position in the world ranking in traffic accidents, considering that the most vulnerable individuals are motorcyclists due to being more exposed to the environment, generating a considerable demand for services of health, resulting in productive loss and high socioeconomic costs, noting that the most common injuries were orthopedic in the lower limbs and neurological, such as traumatic brain injury (TBI), which can lead to inability to perform activities of daily living. It also presents the importance of physiotherapy and the most used techniques, in order to reduce possible sequel, hospitalization time, and reintegrate it into society, offering a better quality of life.